Pain Perception and Management: Where do We Stand? - Afridi, Bilal (Curr Mol Pharmacol, 2021)
BACKGROUND: Pain is often flammable, sharp and sometimes described as an electrical shock. It can be categorized in three different ways as nociceptive, neuropathic and inflammatory. Nociceptive pain always originates in specific situations such as in trauma. Neuropathic pain results in nerve damage. In inflammatory pain, inflammatory mediators are involved in the sensitization of nociceptors. It is important to control the pain as it affects the individual physically, mentally, and socially. OBJECTIVE: Recognizing pain physiopathology and pain pathways, defining the relationship between receptor and transmitter is critical in developing new treatment strategies. In this review, current information on the definitions, classifications, and physiological and chemical mechanisms involved in pain are reviewed. METHODS: Various search engines were used to gather related articles/information. Only peer-reviewed journals were considered. Additional, books/chapters of standard publishers were also included in the article. RESULTS: With a better understanding of the physiological and chemical mechanisms that play a role in pain, significant improvements have been made in pain treatment. Various oral or intravenous drugs, local injection treatments, physical and occupational therapy, electrical stimulation, alternative medicine applications, psychological support, and surgical applications are routinely performed in the treatment, dependent upon the type, severity and cause of the pain. CONCLUSION: Improved understanding of pain physiopathology will serve as the basis for future improvements in the delivery of efficacious and reliable treatments, and is likely to rely on novel technological innovations.